Tractable term-structure models and the zero lower bound - Bruno Feunou; Jean-Sébastien Fontaine; Anh Le; Christian Lundblad (Bank of Canada, 2015)
We greatly expand the space of tractable term-structure models. We consider one example that combines positive yields with rich volatility and correlation dynamics. Bond prices are expressed in closed form and estimation is straightforward. We find that the early stages of a recession have distinct effects on yield volatility. Upon entering a recession when yields are far from the lower bound, (i) the volatility term structure becomes flatter, (ii) the level and slope of yields are nearly uncorrelated, and (iii) the second principal component of yields plays a larger role. However, these facts are significantly different when yields are close to the lower bound. Entering a recession in such a setting, (i) the volatility term structure instead steepens, (ii) the level and slope factors are strongly correlated, and (iii) the second principal component of yields plays a smaller role. Existing dynamic term-structure models do not capture the changes in the cyclical responses of the volatility term structure near the lower bound.
Keywords: G12; 330; Asset pricing; Interest rates; Transmission of monetary policy; Uncertainty and monetary policy; International topics; International financial markets